ANALYSIS OF PROBLEMS IN USING OF ECONOMIC RESOURCES OF COMPANIES IN COVID CONDITIONS - Lakhtionova, Liudmyla Anatoliivna; Sotnyk, Anastasiia Maksymivna (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2021)
The article reveals the nature, components, role and problems of using economic resources of companies in a pandemic COVID-19. Identified some components of economic resources that are most vulnerable to quarantine and complete lockdown. Proposals for eliminating the problems of their use have been revealed, which will ensure the preservation of the successful operation of companies.